PROYEKSI PENGEMBANGAN KELEMBAGAAN DAN KEWENANGAN KECAMATAN MENURUT RPP PEDOMAN ORGANISASI PERANGKAT DAERAH DAN RPP PEMBAGIAN URUSAN PEMERINTAHAN - Meiliana, SE.,MM (Pusjar SKPP Lembaga Administrasi Negara, 2005)
The position of sub-district government in the decentralization era has been essentially altered. Previously it was central government’s agents in charge of deconcentration functions. Since the ‘big bang’ decentralization of 1999, however, it was incorporated to be a part of local government’s bodies. The new pattern of sub-district, certainly, will lead to the needs to rearrange its organizational design and authority. Unfortunately, there is insufficient regulation from central government providing comprehensive guidance and methods on how to revitalize the role, structure and authority of sub-district government. Considering the situation, this paper proposes some alternative options which might be well implemented for creating new configuration of sub-district government.